110k views
4 votes
Solve the equation.√x = x-6x = [?]

1 Answer

4 votes

First step, solve the square root:


\begin{gathered} √(x)=x-6 \\ (√(x))^2=(x-6)^2 \\ x=(x-6)^2 \\ x=x^2-12x+36 \end{gathered}

Now, we group the terms with "x" on the same side:


\begin{gathered} x^2-12x+36-x=0 \\ x^2-13x+36=0 \end{gathered}

Next, we use the quadratic formula to solve the equation:


\begin{gathered} x=(13\pm√(13^2-4*36))/(2) \\ x=(13\pm√(25))/(2) \\ x=(13\pm5)/(2) \\ x=9\text{ or }x=4 \end{gathered}

Hence, the answer is x=9 or x=4

User Michael Celey
by
5.3k points